Distant wars visible : the ambivalence of witnessing - Kozol, Wendy (Critical American studies series, 2014)
'Distant Wars Visible' brings a new perspective to the enduring question about the efficacy of conflict photography and other forms of visual advocacy. In the twenty-first century, visuality has been a pivotal technology in the United States' militaristic pursuit of its national security objectives as well as in critiques of the nation at war. This book analyses both mainstream media and alternative and radical visual projects to understand how representations of U.S. militarism navigate in, through, and around national security logics.